2008
DOI: 10.1111/j.1440-1681.2008.05011.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Dosing Frequency of a Pulmonary Formulation of Tissue Plasminogen Activator Is Well‐tolerated in Mice

Abstract: Summary 1.Tissue plasminogen activator (tPA) has both fibrinolytic and anti-inflammatory activity.These properties may be useful in treating inflammatory lung diseases, such as acute respiratory distress syndrome (ARDS). 2.We have previously demonstrated the feasibility of targeted pulmonary delivery of tPA. As part of our research to develop a clinically viable pulmonary formulation of tPA, we assessed the tolerability and incidence of haemorrhage associated with the administration of a pulmonary formulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 35 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…In this study we showed that tPA, in amounts derived from experimental models, was effective in reducing cast mass ex vivo [10, 15, 25]. This is a reasonable approach for these initial experiments and while this is an encouraging result, much has yet to be done to optimize the pulmonary delivery of this therapeutic protein which appears to have a prolonged elimination in the lungs compared with that of the systemic circulation [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we showed that tPA, in amounts derived from experimental models, was effective in reducing cast mass ex vivo [10, 15, 25]. This is a reasonable approach for these initial experiments and while this is an encouraging result, much has yet to be done to optimize the pulmonary delivery of this therapeutic protein which appears to have a prolonged elimination in the lungs compared with that of the systemic circulation [15].…”
Section: Discussionmentioning
confidence: 99%
“…We report that our PB patients typically produce fibrin, cellular (lymphocytes) casts that are responsive to amounts of tPA that are consistent with those that may be safely delivered to the lungs [10, 15, 25]. …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The stability and function of the mouse formulation (pf-mtPA) was assessed by measuring protein aggregation index (AI), an indicator of protein self-association, by ultraviolet (UV) spectroscopy and fibrinolytic activity as described in previous work [13, 14]. An AI of ≤ 10 was considered optimal.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we have proved the concept of the delivery of active protein in a human lung replica by showing that the nebulized particle size distribution would permit diffuse airway distribution. We have also shown that a maximally feasible dose (3 mg/kg) of pf-tPA can be given repeatedly with increasing frequency over a short period of time without complications [14]. However, the anticipated clinical situation will require prolonged repeated administration of pf-tPA.…”
Section: Introductionmentioning
confidence: 99%